Modeling spatial-polarization parameters of spectral characteristic of cutt-off optical filters - Пецко, Василь Іванович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper gives the summarized changes in parameters of transmission spectra of multilayer interference structures (BIS) of cut-off optical filters depending on the polarization and incidence angle of parallel radiant fluxes relative to the normal to their surface. The model is developed and the effect of the transition region with irregular distribution of the refractive index on the spectral characteristics of the cut-off filters depending on the angle is investigated. The obtained results are particularly relevant for determining the effectiveness of using convergence or divergence of radiation fluxes in optical systems in the presence of BIS. The identified features of spectral characteristics of partially irregular films with different types of refractive index distribution within the section and mathematical modeling of their structure allow to extend the applicability of films of non-crystalline materials in the practice of designing and manufacturing cut-off optical filters.